URBAN MILLENNIAL: ANALYSIS OF URBAN SOCIO-SPATIAL POLICY FOR 'GEN-Y' IN INDONESIA - Agus Mauluddin (CIC Lembaga Riset dan Konsultan Sosial, 2019)
By 2050 about 70% of the world's population will live in cities. Now it is around 54%. In Indonesia, for example, BPS noted that the proportion of Indonesia's population living in urban areas was 49% in 2010 and in 2018 it was around 55%. Interestingly, in 2020 the percentage of the population living in urban areas will be dominated by the millennial generation (in the age range of 20-40 years), who are in fact of the productive age. This trend is inseparable from the urbanization factor (the process of becoming urban). With a literature study: reviews of various international and national journals, as well as literature sources for books and documents, this study argues the need for an urban socio-spatial policy in Indonesia that can adjust urban functions from the response to potential demographic changes that change naturally in society. Urban spatial planning must adjust to the conditions of the urban population, which is dominated by millennial generations. This generation will be an opportunity or vice versa to become a challenge and even a threat to Indonesia's progress in the future.